2006
DOI: 10.1590/s0102-09352006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Listeriose em rebanho de ovinos leiteiros na região serrana do Rio Grande do Sul: relato de caso

Abstract: Relatam-se dois casos de listeriose ocorridos em ovinos leiteiros da raça Lacaune, mantidos em confinamento e alimentados com silagem de milho. O exame histológico do tecido nervoso mostrou meningoencefalite supurada, e a imunoistoquímica foi positiva para Listeria monocytogenes com isolamento da bactéria do tecido nervoso. Enfatiza-se a ocorrência dessa enfermidade em ovinos leiteiros que apresentavam lesões na cavidade oral e eram alimentados com silagem de baixa qualidade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
2
11
0
1
Order By: Relevance
“…This is partially because ruminant listeriosis in Brazil is not of significant economic importance to the national herd considering the reduced levels of occurrence described in cattle, sheep, and goats (Sanches et al , 2000; Guedes et al , 2007; Galiza et al , 2010), and the marked absence of silage and hay feeding of ruminants relative to temperate zones, which makes ruminants in Brazil less susceptible to infection by L. monocytogenes (Headley et al , 2013). Hence, the objective of the current study was to confirm the participation of L. monocytogenes by molecular technique, since there are no reports of small ruminant listeriosis within the state in which these animals were housed, and few descriptions of small ruminant listeriosis in Brazil (Schwab et al , 2004; Ribeiro et al , 2006; Rissi et al , 2006; Guedes et al , 2007; Rissi et al , 2010). Additionally, the hly gene is highly conserved in L. monocytogenes , the primer pairs (Lis1; Lis2) are specie-specific, and differentiates L. monocytogenes from other species of Listeria (Deneer and Boychuk 1991); this further confirms that L. monocytogenes was involved in the brainstem lesions of these animals.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is partially because ruminant listeriosis in Brazil is not of significant economic importance to the national herd considering the reduced levels of occurrence described in cattle, sheep, and goats (Sanches et al , 2000; Guedes et al , 2007; Galiza et al , 2010), and the marked absence of silage and hay feeding of ruminants relative to temperate zones, which makes ruminants in Brazil less susceptible to infection by L. monocytogenes (Headley et al , 2013). Hence, the objective of the current study was to confirm the participation of L. monocytogenes by molecular technique, since there are no reports of small ruminant listeriosis within the state in which these animals were housed, and few descriptions of small ruminant listeriosis in Brazil (Schwab et al , 2004; Ribeiro et al , 2006; Rissi et al , 2006; Guedes et al , 2007; Rissi et al , 2010). Additionally, the hly gene is highly conserved in L. monocytogenes , the primer pairs (Lis1; Lis2) are specie-specific, and differentiates L. monocytogenes from other species of Listeria (Deneer and Boychuk 1991); this further confirms that L. monocytogenes was involved in the brainstem lesions of these animals.…”
Section: Discussionmentioning
confidence: 98%
“…Although this bacterium occurs worldwide, disease in domestic animals is more frequently diagnosed in temperate countries (George 2009). In Brazil, there are few descriptions of listeriosis in domestic animals, with disease occurring in cattle (Schwab et al , 2004; Galiza et al , 2010), sheep (Schwab et al , 2004; Ribeiro et al , 2006; Rissi et al , 2010), and goats (Schwab et al , 2004; Rissi et al , 2006). Data collected from diagnostic laboratories in Brazil have suggested that the occurrence of ruminant encephalitic listeriosis (REL) is significantly reduced (Sanches et al , 2000; Guedes et al , 2007; Galiza et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa doença apresenta baixos índices de morbidade e alta letalidade e nesses casos a infecção geralmente é associada à alimentação com silagem ou contato com fezes ou leite de animais portadores (Vandegraaff et al 1981, Wilesmith & Gitter 1986, George 2002, Rissi et al 2006, Schild 2007. A forma neurológica de listeriose em ruminantes no Brasil já foi descrita em bovinos (Sanches et al 2000), caprinos (Rissi et al 2006, Guedes et al 2007) e ovinos (Mendes et al 2005, Ribeiro et al 2006, Guedes et al 2007), porém não existem descrições detalhadas da forma neurológica da enfermidade em ovinos.…”
Section: Introductionunclassified
“…Regarding Listeria, the presence of this microorganism indicates an environmental contamination (SCHOCKEN-ITURRINO et al, 2005;RIBEIRO et al, 2006), which is very frequent in silages. Of the 10 samples evaluated at 30 days of maturation, three were positive for Listeria.…”
Section: Resultsmentioning
confidence: 99%